A novel sweat sensor detects inflammatory differential rhythmicity patterns in inpatients and outpatients with cirrhosis - Brian C. Davis; Kai-Chun Lin; Sarah Shahub; Annapoorna Ramasubramanya; Andrew Fagan; Sriram Muthukumar; Shalini Prasad; Jasmohan S. Bajaj (npj Digital Medicine)
Abstract Patients with cirrhosis have high systemic inflammation (TNFα, CRP, and IL-6) that is associated with poor outcomes. These biomarkers need continuous non-invasive monitoring, which is difficult with blood. We studied the AWARE sweat-sensor to measure these in passively expressed sweat in healthy people (N = 12) and cirrhosis (N = 32, 10 outpatients/22 inpatients) for 3 days. Blood CRP, TNFα, IL6, levels, and liver function and quality of life were measured. We found that CRP, TNFα, and IL6 were correlated in sweat and serum among both groups and were evaluated in inpatients versus outpatients/controls. IL6 is associated with lower transplant-free survival. Sweat monitoring nocturnal CRP/IL6 elevations in cirrhosis versus controls. Outpatients with cirrhosis had inflammation levels that elevated during the evening and peaked towards the early night periods. The levels start to fall much later at night and early morning. These data suggest that further investigation of continuous measurement of sweat biomarkers in cirrhosis is warranted.